Intercultural Communication between Indonesian and international students at Universitas Padjadjaran - Safi, Abdul Qayoum; Dida, Susanne; Kayen, Hazrat Shah; Shafiq, Khatol (Faculty of Communication Sciences Universitas Padjadjaran, 2022)
Extensive cultural exchanges between ethnicities in the global environment are inevitable, Indonesia included, especially in Educational Institutions. This study aims to evaluate the cross-cultural interaction between Indonesian and International students who enrolled in the same academic environment at Universitas Padjadjaran. It examines cultural distinctions between Indonesian and International students, lecturers, and academic staff. A qualitative approach with case-study methods on cross-cultural communication between Indonesian and International students at Universitas Padjadjaran is applied in this study. The data is collected through interviews with 26 participants, 13 international students of KNB Scholarship 2021, 10 Indonesian students studying at different faculties, and three academic staff at Universitas Padjadjaran. This paper discovered several cultural elements, which are languages, fashion, and cuisine variations, that lead to the development of the international students learning process. In the first year, international students struggle with the cultural gap during their studies. However, they dealt with communication issues through several methods and strategies for an international student to adjust to local culture from the culture shock they experienced at the beginning of their academic journey.